Efektifitas Executive Coaching Pada Tipe Kepemimpinan Transformasional Dan Transaksional - Rauly Sijabat; Pramudianto Pramudianto (Jurnal Administrasi Bisnis, 2019)
Executive coaching that considers leadership types has the potential to change behavior that can improve individual and organizational performance. This is what prompted a study to determine the effectiveness of giving executive coaching on the types of transformational and transactional leadership.The design of the study designed in this study is mixed-factorial design 2x2 between-within subject. The first factor is executive coaching which consists of two levels, namely executive coaching and no executive coaching and the second factor is the type of leadership which consists of two levels, namely transformational and transactional on proactive influence tactics rational persuasion, inspirational appeals, consultation, collaboration. The data measured or observed in this study is the sales performance of the experimental participants consisting of sales heads and key account heads in automotive multinational companies.The findings of this study indicate that this type of transformational leadership with executive coaching has proven to be more effective in improving sales head and key account head sales performance. Furthermore, this study also shows that in the type of transformational leadership, the proactive collaboration and consultation influence tactics proved to be more effective while the transactional leadership type will be more effective in proactive rational and inspirational tactics.